Meningkatkan Efisiensi Operasional Hotel dan Spa melalui Integrasi Sistem Reservasi dengan Interoperabilitas Database - Ariawan, Made Pasek Agus; Peling, Ida Bagus Adisimakrisna; Subiksa, Gde Brahupadhya; Bhaskara, I Made Adi (Jurnal Bangkit Indonesia, 2024)
This research focuses on the crucial role of databases in information management within the Hotel Reservation System and Spa Reservation System. The lack of database integration between these two systems has significant implications for data management, leading to operational errors. The study highlights the challenges of synchronizing reservation information between hotel rooms and spa services as a tangible example of the negative impacts. To address these issues, the implementation of interoperability is proposed for both databases, aiming to facilitate data exchange and integration. These steps are anticipated to mitigate irregularities in information management, enhance coordination between systems, and offer benefits to both operational efficiency and customer satisfaction. The proposed solution reflects efforts to improve the efficiency and data integrity within both information systems. The integration of hotel and spa reservation systems through the merging of ERD diagrams results in an efficient and structured centralized database. The relationships between entities are designed to support data interaction and improve the overall functionality of the system. This integration provides benefits for businesses in terms of efficiency, customer relations, sales, and data analysis.